The use of vegetable oils in the feeding of horses: Review - Nascimento, Nascimento; BIONI, LUCILO BIONI DA FONSECA FILHO; Pereira, Lourival Barros de Sousa Brito; Silva, Tomás Guilherme Pereira; Albuquerque, Priscilla Virginio de; Andrade, Gilcifran Prestes de; Alcantara, Silvia Fernanda de; Silva, Raphael Luiz Andrade; Melo, Felipe Pereira de; Amorim, Marleyne José Afonso Accioly Lins (Pubvet, 2018)
Oils are substances immiscible with water, they can be found in animal, vegetable or mineral forms. Vegetable oils can be obtained from natural seeds, examples include castor bean, canola, soy, buriti, sunflower among others, have triglycerides in their composition, these being formed due to the binding of glycerol molecules with fatty acids. The presence of vegetable oils in the equine diet has become common to the breeder's routine, aiming to increase the digestibility of the animal and for being a source of energy, among the main advantages of the use of vegetable oils in the equine diet can be mentioned decrease in the use of energy for the production of heat by the animal, increase of performance mainly in animal athletes, decrease of food consumption (carbohydrates, which in excess can predispose to laminitis and colic), water, improvement of the body condition of the horse and supply of essential fatty acids. The objective of this literature review is to demonstrate the importance of the use of vegetable oils in the diet of horses, the advantages of introducing vegetable oils and describe how the metabolism occurs in the equine organism. This research field has aroused the interest of several professionals today, focusing mainly on the higher nutritional requirements associated with the better performance of the animals.
Keywords: diet; equine athletes; oily acid; triglycerides